Dowry Amount in Aceh-Indonesia and Selangor-Malaysia: Between State Regulations and Customs - Musyaffa Amin Ash-Shabah; Nahrowi Nahrowi; Masyrofah Masyrofah (AHKAM : Jurnal Ilmu Syariah, 2021)
This study examines the legal considerations in settling inheritance disputes involving land distribution in Selong Religious (Islamic) Court of East  Nusa Tenggara. The data in this study were obtained from interviews and court decision analysis. This study shows that the practice of granting property before the death of the muwārith (testator) can cause inheritance-based land disputes in the future. Disputes usually arose when the land was distributed only to particular heirs, neglecting the others, especially the daughters and their descendants. In deciding the land disputes in inheritance cases, judges evermore considered the legal validity of the land distribution. Besides that, the judges use Islamic legal sources such as the Quran, Hadith, opinions of scholars, and fiqh in their legal considerations. However, the use of these multiple references does not necessarily lead to a diverse outcomes.   Abstrak: Penelitian ini membahas praktik pemberian mahar dalam perkawinan masyarakat Aceh, Indonesia dan Selangor, Malaysia. Studi ini mengkaji ketentuan kadar mahar dalam perundang-undangan Indonesia dan Malaysia serta penerapannya di tengah masyarakat. Sumber data dalam penelitian hukum empiris ini adalah wawancara dan studi dokumen. Data-data tersebut kemudian diolah menggunakan teori realisme hukum dan teori ‘urf. Temuan dalam penelitian ini menjelaskan bahwa ketentuan kadar mahar dalam perundang-undangan Indonesia berdasarkan asas kesederhanaan dan kemudahan. Namun, dalam praktiknya aturan adat Aceh menjadi pilihan masyarakat dalam menentukan dan menetapkan kadar mahar. Penetapan kadar mahar di Aceh ditentukan oleh pihak keluarga perempuan yaitu mahar mitsl, yang diberikan dalam bentuk emas dengan sebutan mayam. Berbeda dengan kadar mahar Negeri Selangor yang ditentukan oleh Pemerintah Kerajaan Negeri dengan kadar minimum RM 300.00 yang merupakan kesatuan antara mahar dan hantaran untuk gadis maupun janda. Kenyataannya di masyarakat terdapat beberapa orang Selangor yang masih menetapkan sendiri nilai hantaran yang harus diserahkan kepada pihak perempuan.